Studien zum Verhältnis von Literatur und Moral an ausgewählten Werken des schweizerischen bürgerlichen Realismus - Grossenbacher, Thomas (Haupt, 1984)
Study of the work of Jeremias Gotthelf and Conrad Ferdinard Meyer, and of Gottfried Keller's Der grüne Heinrich.
Keywords: Gotthelf, Jeremias -- 1797-1854; Keller, Gottfried -- 1819-1890; Meyer, Conrad Ferdinand -- 1825-1898; Geschichte 1800-1900; Geschichte 1841-1891; Literature and morals; Realism in literature; Swiss fiction (German) -- 19th century -- History and criticism; Moral; Prosa; Roman; Deutsch; Realismus; Moral -- Motiv; Ethik; Schweiz